Penerapan Algoritma Genetika Untuk Penjadwalan Mengajar Guru (Studi Kasus: SD Negeri Kunciran 7) - Binsar (PT Triputra Sejahtera Prima, 2025)
Teacher scheduling in schools often faces various challenges that can disrupt the learning process. One of the main issues is the occurrence of schedule conflicts, especially when a teacher is assigned to teach multiple classes. At SD Negeri Kunciran 7, scheduling is still done using Microsoft Excel, which is time-consuming and prone to errors. To address this problem, this study implements a web-based scheduling system using the Genetic Algorithm. The Genetic Algorithm is chosen due to its ability to solve optimization problems involving multiple variables and constraints, such as the number of teachers, classes, subjects, and limited time slots. Through stages such as initial population generation, fitness evaluation, selection, crossover, and mutation, the system is able to produce optimal teaching schedules, minimize conflicts, and accelerate scheduling. The testing results show that this algorithm can be effectively used to support efficient and accurate scheduling.